2016
DOI: 10.1016/j.antiviral.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mice against the highly pathogenic VVIHD-J by DNA and fowlpox recombinant vaccines, administered by electroporation and intranasal routes, correlates with serum neutralizing activity

Abstract: Please cite this article as: Bissa, M., Quaglino, E., Zanotto, C., Illiano, E., Rolih, V., Pacchioni, S., Cavallo, F., De Giuli Morghen, C., Radaelli, A., Protection of mice against the highly pathogenic VV IHD-J by DNA and fowlpox recombinant vaccines, administered by electroporation and intranasal routes, correlates with serum neutralizing activity, Antiviral Research (2016Research ( ), doi: 10.1016Research ( / j.antiviral.2016 This is a PDF file of an unedited manuscript that has been accepted for publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…It is known that, although many epitopes of ZIKV are very similar to those of other flaviviruses, higher concentrations of antibodies are needed for virus neutralization compared to other flaviviruses [29]. We have also previously demonstrated that the specific neutralizing response may be hidden by the aspecific activity, detected in naïve mice or in control mice immunized with irrelevant immunogens [44]. However, our previous study showed that vaccinated mice can be protected and survive also when a very low neutralization titer is used, with an increase in specific vs aspecific antibodies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is known that, although many epitopes of ZIKV are very similar to those of other flaviviruses, higher concentrations of antibodies are needed for virus neutralization compared to other flaviviruses [29]. We have also previously demonstrated that the specific neutralizing response may be hidden by the aspecific activity, detected in naïve mice or in control mice immunized with irrelevant immunogens [44]. However, our previous study showed that vaccinated mice can be protected and survive also when a very low neutralization titer is used, with an increase in specific vs aspecific antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…After deletion of the A27L gene from pFP A27L recombination plasmid [43,44] and subcloning of the cPrME fragment, the resulting pFPcPrME18 clone was sequenced to exclude any possible mistakes due to the PCR amplification. A non-synonymous mutation at nucleotide 759, where the cytosine nucleotide had replaced the thymine giving origin to an alanine instead of a valine, was corrected by site-specific mutagenesis [45,46].…”
Section: Recombination Plasmidmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination experiments performed in mice indicated that FWPV recruited a significantly smaller portion of the unfavorable CD11b Ϫ CD103 ϩ but elevated levels of favorable CD11b ϩ CD103 Ϫ dendritic cells to lung tissue than MVA or vaccinia virus (44). FWPV-based vaccines, administered in combination with a DNA prime, have been reported to induce neutralizing antibodies (45,46) and strong CD4 ϩ and CD8 ϩ T-cell responses (23-25, 30, 47, 48). Therefore, they have been considered for vaccination against cancer in humans (47,49,50) and against a variety of viral infections in different species (31,32,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…FWPV-based vaccines, administered in combination with a DNA prime, have been reported to induce neutralizing antibodies (45,46) and strong CD4 ϩ and CD8 ϩ T-cell responses (23-25, 30, 47, 48). Therefore, they have been considered for vaccination against cancer in humans (47,49,50) and against a variety of viral infections in different species (31,32,45,46). Both vaccination regimes used in our study resulted in significantly reduced peak viremia and reduced set point viral load after infection compared to controls.…”
Section: Discussionmentioning
confidence: 99%